504 Can Measuring Heart Rate Variability in The Operating Surgeon Provide Insight into Intra-Operative Stress? A Literature Review and Direction for Research. (4th May 2021) - Pearson, L; Narayanan, A; Fisher, J P; Khashram, M
Abstract: Introduction: Stress affects the internal environment of the operating surgeon. Examining ways to mitigate this could prove important to the health of both surgeon, and patients. Heart rate variability (HRV) is emerging as a novel, validated measure of autonomic nervous system (ANS) function with developing accessible and non-invasive technologies. HRV parameters correlate to ANS function and can be used to measure responses to various stimuli. Method: A search strategy was developed to identify 23 articles that matched inclusion criteria. These included data collected intra-operatively with ambulatory monitoring, in simulated settings and one systematic review. Results: Several studies found increased sympathetic response in the operating surgeon – which correlates with subjective reporting of stress. Some studies compared variables; one study suggested that laparoscopic colorectal surgery caused higher mental strain than open, while another suggested higher stress in surgeons while teaching compared to when primary operator. There have been no comparative trials using HRV in surgeons. Conclusions: We present a review of the growing literature regarding HRV measurement in surgeons. This novel tool is a promising avenue to provide psychophysiological insight into the operating surgeon. This could guide future research into optimising the theatre environment for intra-operative performance using controlled or in-situ design.